Political Connection, Financial Distress and Cost of Debt: Empirical Evidence from Emerging Country - Hadiputra, Antonius Arya; Windijarto (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2023)
Objective: This study aims to investigate the impact of political connections on financial distress and the firm's cost of debt. Design/Methods/Approach: The research sample is all companies listed on the Indonesia Stock Exchange from 2010 to 2021, with 3072 observations obtained from OSIRIS Database. This study uses a quantitative approach with panel data regression analysis using E-Views 12 software program to test the hypothesis. Findings: The results indicate that political connections significantly adversely affect financial distress, while political connections do not affect the cost of debt. In addition, this study also divides companies based on the nature of their political connections. Companies with political connections from the central government, local government, and the military affect financial distress. Meanwhile, only political connections from executive government employees and political connections from families affect the company's cost of debt. Originality: This research developed the political connection based on its nature to measure the effect of political connection on financial distress and the cost of debt. It extends the previous understanding of the impact of political connections. Policy implication: The findings are relevant for companies and other stakeholders to be more aware and utilize political connections to make better decisions and for the government to develop guidelines for better disclosure of political connections.